Efforts to Improve Students' Understanding of Islamic Religious Education Learning Through the Student Teams Achievement Divisions Cooperative Learning Model in Elementary Schools - Nailatur Rizqiyah; Masti Yanto; Saiful Arif; Siti Mudawwamatul Islamiyah (Indo Publishing, 2025)
This research was motivated by the challenge of PAI teachers in increasing fifth grade students' understanding of PAI material at SDN Kowel 3 Pamekasan. The aim of this research is to increase students' understanding of learning material through the Student Teams Achievement Divisions type cooperative learning model. This research is a type of classroom action research (PTK) which is carried out in 2 cycles consisting of several stages including: planning, implementation, observation and reflection. The subjects of this research were 21 class V students of SDN Kowel 3 Pamekasan. The data taken is the result of observations obtained from observations of the learning process. The results of this research indicate that the application of the Student Teams Achievement Divisions type cooperative learning model can improve students' understanding of the material being studied. This can be seen from the percentage of classical completion which shows that from cycle to cycle there is an increase. In cycle 1 the percentage of classical completion was 57% and in cycle 2 it was 76.2%. This can also be seen from the increase in class average scores in cycles 1 and 2, namely 0.8 and 2.